E-literacy in Indonesian Society Regarding Covid-19 - Zata Ismah; Andini Nur Bahri; Irna Khairani Siregar; Dhyta Taniya Abdika Pane; Suhendri Suhendri (LPPM Universitas Jambi, 2021)
During the Covid-19 pandemic, it is very necessary to carry out e-literacy because in addition to the spread of the Covid-19 virus the community was also faced with a lot of false information that was widespread on social media. One way that can be done to break the chain of spreading hoaxes is the skill of e-literacy. The aim of this study is to describe the access to e-literacy in Indonesian society regarding the Covid-19 vaccine. The research method used is descriptive with a cross sectional design, the study population is the Indonesian people as many as 2,759 people. Sources of data is primary data were obtained from questionnaires. The data analysis technique used descriptive statistics. Based on the results of the analysis in this study, the respondents responded related to e-literacy covid future pandemic-19, respondents stated the most difficult using information about the vaccine virus that find on the internet for the other (14.9%); difficulty making health decisions based on information from the Internet. Meanwhile (31.4%), it is easy to apply information from the Internet about the Covid-19 Vaccine (49.3%). And it is very easy to find information about the corona virus vaccine on the Internet (48.3%). Overall, the Indonesian people already understand the importance of e-literacy related to the Covid-19 pandemic. The public can already judge the good or bad information they get and can decide which information to absorb to protect themselves from the threat of Covid-19.